Hand grip strength vs. sprint effectiveness in amputee soccer players - Wieczorek, M.; Wilinski, W.; Struzik, A.; Rokita, A. (Journal of Human Kinetics, 2015)
Amputee soccer is one of the types of soccer designed for the disabled, especially those who have undergone amputations, as well as those with extremity dysfunction. The objective of the study was to find the relationship between hand grip strength and sprint time in amputee soccer players. Thirteen field amputee soccer players participated in the study. A SAEHAN hydraulic hand dynamometer manufactured by Jamar was used for hand grip strength measurements. The sprint running test was conducted over a distance of 30 m. The Fusion Smart Speed System was employed for running time measurements. No statistically significant relationships were found between hand grip strength of the left or right hand, and sprint times over 1, 5, 10, 15, 20, 25 and 30 m. Analysis of the running velocity curve of the subjects showed an interesting profile characterized by a 15 meter-long acceleration phase and a significant velocity increase over a distance of 20 - 25 m. The study suggests that there is no relationship between hand grip strength and sprint effectiveness in amputee soccer players. The specificity of locomotion with the use of elbow crutches among elite Polish amputee soccer players probably accounts for the profile of the sprint velocity curve. Extension of the acceleration phase in the sprint run and a velocity increase in the subsequent part of the run were observed.